Unique heating curves generated by radiofrequency electric-field interactions with semi-aqueous solutions - Lara, Nadia C; Haider, Asad A; Wilson, Lon J; Curley, Steven A; Corr, Stuart J (Applied physics letters, 2017)
Aqueous and nanoparticle-based solutions have been reported to heat when exposed to an alternating radiofrequency (RF) electric-field. Although the theoretical models have been developed to accurately model such a behavior given the solution composition as well as the geometrical constraints of the sample holder, these models have not been investigated across a wide-range of solutions where the dielectric properties differ, especially with regard to the real permittivity. In this work, we investigate the RF heating properties of non-aqueous solutions composed of ethanol, propylene glycol, and glycine betaine with and without varying amounts of NaCl and LiCl. This allowed us to modulate the real permittivity across the range 25-132, as well as the imaginary permittivity across the range 37-177. Our results are in excellent agreement with the previously developed theoretical models. We have shown that different materials generate unique RF heating curves that differ from the standard aqueous heating curves. The theoretical model previously described is robust and accounts for the RF heating behavior of materials with a variety of dielectric properties, which may provide applications in non-invasive RF cancer hyperthermia.